(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Because they aid in the administration of justice, witnesses are an important part of a well-functioning criminal justice system. In judicial proceedings, witnesses and their role in determining case outcomes are crucial. Hostile witnesses, on the other hand, have become a concern since they are the major source of high acquittal rates for offenders accused of terrible crimes such as murder, rape, and other crimes. When a favourable witness turns hostile, it creates a challenging situation that might have an impact on the case’s result. After being threatened and pressured by the accused or his or her family members, they alter their views before or during the trial. This can lead to a miscarriage of justice or even justice’s death. Society will lose trust in the judicial system if no efforts are taken to avoid hostile witnesses, culminating in anarchy. Because they are no longer afraid of the law, suspects can conduct crimes without fear of penalties due to the lack of witness protection regulations. The purpose of this article is to examine the role of the courts in safeguarding a hostile witness. It looks at the problem of hostile witnesses and how they affect the judicial system. It sought to understand why and under what conditions witnesses become hostile. The study also examines the concept of witness protection in light of key legislative laws and the judiciary’s opinions on witness protection. For the purpose of doing research on the subject, the Doctrinal technique was used. The research was descriptive and explanatory, and it looked at the function of the judiciary in safeguarding hostile witnesses. For a clear view on the study paper, normative research was done in which many books, as well as many websites and articles, were consulted.